Managing the conflicts between regulatory goals - Payne, J (Oxford University Press, 2024)
Policymakers make use of a range of regulatory goals, some of which are articulated, and some of which are not. Conflicts between regulatory goals can arise and therefore having mechanisms in place to resolve these conflicts is important. Regulatory goals may vary from jurisdiction to jurisdiction and may change over time as economic and political narratives develop. This chapter examines the regulatory goals that have developed in the EU context, considers the ways in which these goals can come into conflict and analyses the consequences of these conflicts. It argues that regulators need to have in place a process for identifying and resolving conflicts between regulatory goals. In terms of identifying conflicts, it is suggested that within the EU this can be done by utilizing and expanding the existing regime of impact assessments, evaluations and fitness checks which are designed to provide ex ante and ex post assessments of legislative instruments. In terms of resolving these conflicts it is suggested that a strict hierarchy of regulatory goals, while superficially attractive as a mechanism for resolving conflicts, has a number of disadvantages, and that instead a more holistic approach should be adopted by policymakers. This is an important issue. Difficulties can arise where conflicts are unresolved, but also where the conflict is resolved inappropriately by giving undue precedence to one goal over another, as this chapter discusses. Dealing with this issue effectively will improve the quality of the EU legislative process.